Baroque and rococo - Bailey, Gauvin A. (Art and ideas, 2012)
The baroque, as we now call it, was an international artistic revolution that swept from late sixteenth-century Italy, throughout Europe, and into Russia, the Americas, colonial Africa and Asia during the seventeenth century. Combined with the Rococo -its equally global, later variant- it defined visual style and popular taste until the end of the eighteenth century. Never before had the arts focused so intensely on their impact on the viewer, whether it was the drama of aswirling Cortona ceiling, the intensity of a Caravaggio altarpiece, the sensitivity of a Rembrandt portrait, the passion of a Bernini sculpture, the serenity of a Claude landscape, or the grandeur of Versailles. Arts of all forms enthralled and impressed with vitality and emotion that still resound today. This book explores the core elements of the styles throughout all types of manifestation across the world, presenting a uniquely wide-ranging and refreshing survey of this remarkable period. The painters, sculptors, ceramicists, landscapists, print-makers, furniture-makers, interior designers, and architects included are represented by well-known masterpieces as well as more obscure, but nonetheless superlative, examples of the essence of the Baroque and the Rococo.